Analisis Pengelolaan Data Pengadaan Barang dan Jasa Berbasis LPSE dalam Kerangka Satu Data Indonesia: Studi Kasus Magang di Biro PBJ Provinsi Sumatera Selatan - Chairul Anwar (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
This study examines the management of public procurement data through the Electronic Procurement Service (Layanan Pengadaan Secara Elektronik/LPSE) within the framework of Satu Data Indonesia (One Data Indonesia), based on an internship conducted at the Bureau of Goods and Services Procurement (Biro Pengadaan Barang dan Jasa) of the Secretariat of South Sumatra Province from October to December 2025. Satu Data Indonesia requires government data to follow common data standards, metadata, interoperable formats, and a single reference code, yet procurement data recorded through LPSE and related systems such as SIRUP is often produced with inconsistent column terms and formats before it can be integrated into the provincial Satu Data dashboard. This study used a qualitative descriptive case-study approach, with data obtained through participatory observation, document study, and an internal dataset of procurement packages, funding sources, and procurement officials recorded during the internship. The results show that of 65 regional agencies recorded, a total of 6,912 procurement packages were logged for 2025, dominated by the Tourism and Culture Office with 808 packages, while 13 agencies still show zero recorded packages, indicating uneven data readiness across agencies. Terminology and format mismatches, together with a dashboard input table that was not yet available during the first half of the internship, were the main obstacles to timely data integration. The study recommends simplifying data-entry terminology, providing clearer technical guidance for data verification, and strengthening the interoperability mechanism between LPSE, SIRUP, and the provincial Satu Data portal to support more transparent and accountable procurement governance.